Fighting the Current: The Rise of American Women's Swimming, 1870-1926 - Bier, Lisa (McFarland & Co., 2011)
"This book describes the origins of women's competitive swimming in the United States. Women faced many obstacles to safe swimming opportunities, including restrictive beliefs about physical abilities, access to safe clean water, bathing suits that did not allow for movement, and opposition from official sporting organizations. This book is a testament to how far female athletes have come"--Provided by publisher.
Keywords: Ederle, Gertrude, 1906-2003; Olympic Games (7th : 1920 : Antwerp, Belgium); Olympic Games (8th : 1924 : Paris, France); Swimming for women; History; History; Swimming; United States; dept.lib; faculty_collection

Handheld libraries 101 using mobile technologies in the academic library - Kosturski, K.; Skornia, F (Computers in Libraries, 2011)
Keywords: dept.lib; ⛔ No DOI found

Trendspotting 2011 - Thomas, L.C. (Journal of Web Librarianship, 2011)
Keywords: dept.lib

Max Ernst Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Qarrtsiluni Online Literary Magazine, 2011)
Keywords: dept.lib

[Seven Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (The Dirty Goat, 2011)
Keywords: dept.lib

Building blocks for personal brands - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2011)
Keywords: dept.lib

Design for double rainbow - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2011)
Keywords: dept.lib

Google+ and the commodification of cool - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2011)
Keywords: dept.lib

Libraries, librarians and mobile services - Thomas, Lisa Carlucci (Bulletin of The American Society for Information Science and Technology, 2011)
Keywords: dept.lib

Technical service outreach strategies for academic libraries - Toce, Jacqueline; Schofield, Cindy (Technical Services Quarterly, 2011)
The model of a library staff divided into technical and informational service divisions remains common-especially among academic libraries. The authors argue that in many ways it is now the technical services division that is best positioned to provide outreach services to a community-whether at the university or municipal level. Maintaining bibliographic access amid the changing information landscape hinges on a clear understanding of systems, metadata, and traditional organizational skills, all home grown in the back rooms of conventional libraries. The authors cite examples of library outreach that emanated from technical service departments and conclude that the sequestered staffs of the past must make themselves indispensible today by sharing their knowledge and talents, offering services to their communities that require their technical expertise, and advance the mission of the library organization. © Taylor & Francis Group, LLC.
Keywords: Academic libraries; Catalogers; Cooperative; Outreach; Service; Southern connecticut state university; Technical services; dept.ils; dept.lib